Effect of Oral and Dental Health on Combat Fitness- A Study Conducted in Military Dental Centre Cumilla (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: The effect of oral and dental diseases of the deployed troops can seriously impair the operational activity. Combat fitness on oral and dental aspect means keeping soldier’s oral health in such a state so that they can be quickly deployed, as well as military dental personnel staying in such a way that they can be moved in the front with all of their equipment and materials to treat patients.Objective: To figure out the present oral health status of Bangladeshi troops and to correlate it’s possible influence on combat situation.Methods: This descriptive study was carried out in Military Dental Centre Cumilla from 01 March 2020 to 31 March 2022. All uniformed personnel reported to MDC with oral and dental issues were included in this study.Results: A total of 4597 uniformed personnel were evaluated and treated. Among them sainik and lance corporals were highest 2289(50%). Dental caries was mostly diagnosed condition 1410(31%). In case of acute dental condition irreversible pulpitis cases were most in number 420(35%). Dental restoration was mostly performed procedure 1293(48%) and glass ionomer restoration was done 830(64%) in most of the cases. The dental emergency rate was 230 per 1000 soldier per year.Conclusion: Disease non battle injury (DNBI) originating from dental pathologies obviously compromise the performance of high intensity missions. In this study, number of dental emergency rate (considering every dental visit) was found 230 per 1000 soldiers per year which is very similar to other countries.JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 16-20